2020
DOI: 10.1111/aej.12407
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐operative ketorolac efficacy with different anesthetics, irrigants during single visit root canal treatment of mandibular molars with acute irreversible pulpitis

Abstract: Mandibular molar teeth with acute irreversible pulpitis pose challenges in single visit root canal treatment – (i) success of local anaesthesia and (ii) post‐operative pain. One hundred and twenty‐six patients with pain associated with carious mandibular molar teeth were enrolled. All patients were administered 10 mg of ketorolac tromethamine prior to local anaesthesia. Local anesthetics used were 2% lignocaine with 1:80 000 adrenaline and 4% articaine with 1:100 000 adrenaline. Three irrigation solutions were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 17 publications
3
7
1
Order By: Relevance
“…An earlier report from the authors’ department concluded that pre-operative ketorolac tromethamine was not effective in reducing the intra-operative pain for mandibular molar teeth with acute irreversible pulpitis and apical periodontitis when using inferior alveolar nerve blocks (IANB) with both lignocaine and articaine anesthetic agents. However, it was effective in reducing post-operative pain after using lignocaine which was in agreement with a meta-analysis (3, 4). Mean intra-operative pain scores for both anesthetic agents were 4.33 and 4.22, respectively, and 27 (21.4%) patients required supplemental anaesthesia to control their intra-operative pain in the aforementioned study (3).…”
Section: Introductionsupporting
confidence: 89%
See 4 more Smart Citations
“…An earlier report from the authors’ department concluded that pre-operative ketorolac tromethamine was not effective in reducing the intra-operative pain for mandibular molar teeth with acute irreversible pulpitis and apical periodontitis when using inferior alveolar nerve blocks (IANB) with both lignocaine and articaine anesthetic agents. However, it was effective in reducing post-operative pain after using lignocaine which was in agreement with a meta-analysis (3, 4). Mean intra-operative pain scores for both anesthetic agents were 4.33 and 4.22, respectively, and 27 (21.4%) patients required supplemental anaesthesia to control their intra-operative pain in the aforementioned study (3).…”
Section: Introductionsupporting
confidence: 89%
“…However, it was effective in reducing post-operative pain after using lignocaine which was in agreement with a meta-analysis (3, 4). Mean intra-operative pain scores for both anesthetic agents were 4.33 and 4.22, respectively, and 27 (21.4%) patients required supplemental anaesthesia to control their intra-operative pain in the aforementioned study (3). In another clinical study in the authors’ department where an inferior alveolar nerve block was used plus buccal nerve infiltration and intra-ligamentary injection with both anesthetic agents for single-visit root canal treatment in mandibular molar teeth with acute irreversible pulpitis, the mean intra-operative pain scores were 2.43 and 3.19 for the two anesthetic agents, respectively, and 12 (9.4%) patients required supplemental anesthesia (5).…”
Section: Introductionsupporting
confidence: 89%
See 3 more Smart Citations